Gender differences in payment for labour: a regional aspect - N. V. Borоvskikh (Вестник СибАДИ, 2017)
The authors present an analysis of labour market and prognosis of its development in Omsk region. The authors have analyzed three groups of factors influencing gender differences in a salary on the region’s level, gender differences in human capital, concentration of employed men and women in various sectors of economy, professions and positions. The authors also give attention to women’s discrimination on the labour market.